Glossary for econometrics and epidemiology. Issue 10 (12th September 2008) - Gunasekara, F Imlach; Carter, K; Blakely, T
Abstract : Epidemiologists and econometricians are often interested in similar topics—socioeconomic position and health outcomes—but the different languages that epidemiologists and economists use to interpret and discuss their results can create a barrier to mutual communication. This glossary defines key terms used in econometrics and epidemiology to assist in bridging this gap.